Synthesis of epichlorohydrin from glycerol - Herliati (2013)
Glycerol is the main byproduct of the biodiesel production. Recently, the market has been flooded by the crude natural glycerol due to the rapid growth in biodiesel industry. Since this crude glycerol has a very low value because of its impurities, the development of new technology to convert glycerol to more valuable chemicals is become an interesting study. Among the various possibilities, a technology to convert glycerol to epichlorohydrin has caught our attention. Epichlorohydrin produce 1,3-dichloropropanol (1,3-DCP) in the presence of carboxylic acid as the catalyst. The next stage is dehydrochlorination reaction where 1,3-DCP produced from the previous reaction was reacted with sodium hydroxide (NaOH) to form EPCH without the presence of any catalyst. This study includes both simulation and experimental works. Process simulation is crucial in many chemical process development studies to facilitate the analysis, and optimization of technical processes. It allows the designer to test the performance of process under different conditions and provide feedback quickly. In this study, process simulations were conducted prior the experimental study on both the 1,3-dichloropropanol preparation, and the epichlorohydrin preparation using the ASPEN PlusTM simulation software. The synthesis of 1,3-dichloropropanol occurred through hydrochlorination process, was modeled and simulated using RBatch block which is suitable for a semi-batch reactor process (SBSTR). The simulation was conducted at different temperatures (80 to 120oC); different molar ratio and different concentration carboxylic acid catalyst at atmospheric pressure. The optimum temperature, optimum molar ratio glycerol:HCl, and optimum concentration of the catalyst were found at 110oC, 1:16, and 8 percent by mol of glycerol fed respectively. Subsequently, the synthesis of epichlorohydrin took place via dehydrochlorination reaction was simulated using the reactor block RBatch at different temperatures (20 to 60 oC) and atmospheric pressure without presence of catalyst. The optimum temperature and optimum molar ratio 1,3-DCP:NaOH were found 60oC (333 K) and stoichiometric respectively. The results from simulation studies shed insights of the performances of these reactions in terms of conversion, (EPCH), an important raw material for the production of epoxide resins was successfully synthesized via two-stage process. The first stage is hydrochlorination reaction of glycerol with aqueous hydrogen chloride as a chlorination agent to selectivity and yield. The results from these simulations were used to minimize the experimental and scale-up efforts and enable the process optimization to be conducted in wider range of conditions which might not be possible by the experimental study. Experimental study on hydrochlorination reaction was carried out under operating temperatures ranged from 80 to 120oC and atmospheric pressure, reactant molar ratio from 1:16 to 1:32, and different types of carboxylic acid catalyst. The amount of catalyst required was 8 percent by mol of the total mol of glycerol intake. The optimal reaction conditions were: temperature, 110oC; reactant molar ratio glycerol to HCl, 1:24; catalyst, malonic acid; duration, 3 hours. Quantitative analyses of the reaction products were performed using GC-MS. Furthermore, experimental studies on dehydrochlorination reaction were carried out under temperatures (50 to 80oC) and reactant molar ratios (1:1 to 1:9). Basic solution of NaOH was added in the reactor, followed by 1,3-DCP as soon as the reaction temperature was reached. The optimal reaction conditions were: temperature, 70oC; reactant molar ratio 1,3-DCP to NaOH, 1:5; duration at 3 minutes. Analysis of the reaction products was also performed using GC-MS. The kinetics study on dehydrochlorination of dichloropropanol and sodium hydroxide to epichlorohydrin was investigated. The effect of temperatures (50 to 80oC) at different times on such reaction was observed. The reaction rate was found to be pseudo first order with respect to dichloropropanol concentration. The reaction rate constants at these temperatures were 0.0056; 0.008; 0.012; and 0.021 respectively. Subsequently, the activation energy was determined at 38.85 kJ/mol and the pre-exponential factor A was 1.62 x 104 sec-1. In the presence of excess water and at temperature above 70oC, epichlorohydrin can be easily converted to glycerol thus lower the yield of epichlorohydrin. Therefore, not only choosing the optimal operating conditions but maintaining low amount of water and short contact time are important factors in the design of the reactor for epichlorohydrin of DCP.